Anti-communal, Anti-egalitarian, Anti-nurturing, Anti-loving: Sex and the 'Irredeemable' in Andrea Dworkin and Catharine MacKinnon. Issue 3 (November 2018) - Dymock, Alex
Abstract : The work of Andrea Dworkin and Catharine A. MacKinnon on sex and sexuality has often been posed as adversary to the development of queer theory. Leo Bersani, in particular, is critical of the normative ambitions of their work, which he sees firstly as trying to 'redeem' sex acts themselves, and secondly as advocating for sexuality as a site of potential for social transformation. In this article, I argue that this is a misreading of their work. Drawing on Dworkin's wide body of writing, and MacKinnon early essays in Signs, I suggest that their work makes no such case for sex or sexuality. Rather, by bringing their analysis into conversation with Halberstam's recent work on 'shadow feminism', I contend that Dworkin and MacKinnon's antisocial, anti-pastoral and distinctly anti-normative vision of sex and sexuality shares many of the same features of queer theory, ultimately advocating for sex as 'irredeemable'.